2022
DOI: 10.1002/adhm.202202224
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Approaches to Delineate the Metabolic Regulation of Tumor Invasion by Hyaluronic Acid Biosynthesis

Abstract: Metastasis is the leading cause of breast cancer‐related deaths and is often driven by invasion and cancer‐stem like cells (CSCs). Both the CSC phenotype and invasion are associated with increased hyaluronic acid (HA) production. How these independent observations are connected, and which role metabolism plays in this process, remains unclear due to the lack of convergent approaches integrating engineered model systems, computational tools, and cancer biology. Using microfluidic invasion models, metabolomics, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Using this approach, we demonstrated previously that overproduction of hyaluronic acid (HA) by cancer stem-like cells increases their invasion into a 3D collagen matrix due to elevated glycolytic metabolism. 38 As EC-secreted factors also increased tumor cell invasion and glycolytic metabolism, we speculated that changes in tumor cell stemness may underlie these observations. Interestingly, exposure of MDA-MB-231 reporter cells that express green fluorescent protein (GFP) under control of the stem cell transcription factor NANOG (GFP-NANOG) to HUVEC-CM increased the fraction of GFP high , stem-like cells relative to treatment with CTRL-CM [Figs.…”
Section: Resultsmentioning
confidence: 95%
“…Using this approach, we demonstrated previously that overproduction of hyaluronic acid (HA) by cancer stem-like cells increases their invasion into a 3D collagen matrix due to elevated glycolytic metabolism. 38 As EC-secreted factors also increased tumor cell invasion and glycolytic metabolism, we speculated that changes in tumor cell stemness may underlie these observations. Interestingly, exposure of MDA-MB-231 reporter cells that express green fluorescent protein (GFP) under control of the stem cell transcription factor NANOG (GFP-NANOG) to HUVEC-CM increased the fraction of GFP high , stem-like cells relative to treatment with CTRL-CM [Figs.…”
Section: Resultsmentioning
confidence: 95%
“…Due to the ubiquity of HA in the brain tissue and tumor microenvironment, several research groups have reported in recent years the role of hyaluronan as a nutrient in tumor progression (7,9,39). Moreover, research has revealed that mitochondrial DNA content is related to survival and that tumor cells activate compensatory pathways to maintain the mitochondrial metabolism (40,41), uncovering the possibility of promising combinatorial treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the ubiquity of HA in the brain tissue and tumor microenvironment, several research groups have reported in recent years the role of hyaluronan as a nutrient in tumor progression (7,9,39).…”
Section: Hyaluronan-regulated Changes In Gbm Mitochondrial Respirationmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, culture on CDMs also increased surface-associated HA on tumor cells relative to TCP, a characteristic that has been shown previously to contribute to stemness and invasion (Figure S3B). 57 To further assess whether culture on CDMs stimulates a stem-like phenotype in tumor cells, we performed a limited dilution assay in which MDA-MB-231 cells were first precultured on either TCP or CDMs and subsequently maintained in serum-free, nonadherent conditions. While cells precultured on CDMs and seeded at high densities formed more spheres than cells precultured on TCP, these changes did not translate to an increase in self-renewal as determined using the extreme limited dilution analysis (ELDA) 58 (Figure S3C,D).…”
Section: Cells Migrate Further On Cdmsmentioning
confidence: 99%